Development of Natural Active Agent-Containing Porous Hydrogel Sheets with High Water Content for Wound Dressings - Thanyaporn Pinthong; Maytinee Yooyod; Jinjutha Daengmankhong; Nantaprapa Tuancharoensri; Sararat Mahasaranon; Jarupa Viyoch; Jirapas Jongjitwimol; Sukunya Ross; Gareth M. Ross (Gels, 2023)
This work was concerned with the fabrication of a porous hydrogel system suitable for medium to heavy-exudating wounds where traditional hydrogels cannot be used. The hydrogels were based on 2-acrylamido-2-methyl-1-propane sulfonic acid (AMPs). In order to produce the porous structure, additional components were added (acid, blowing agent, foam stabilizer). Manuka honey (MH) was also incorporated at concentrations of 1 and 10% w/w. The hydrogel samples were characterized for morphology via scanning electron microscopy, mechanical rheology, swelling using a gravimetric method, surface absorption, and cell cytotoxicity. The results confirmed the formation of porous hydrogels (PH) with pore sizes ranging from ~50–110 µm. The swelling performance showed that the non-porous hydrogel (NPH) swelled to ~2000%, while PH weight increased ~5000%. Additionally, the use of a surface absorption technique showed that the PH absorbed 10 μL in <3000 ms, and NPH absorbed <1 μL over the same time. Incorporating MH the enhanced gel appearance and mechanical properties, including smaller pores and linear swelling. In summary, the PH produced in this study had excellent swelling performance with rapid absorption of surface liquid. Therefore, these materials have the potential to expand the applicability of hydrogels to a range of wound types, as they can both donate and absorb fluid.